EMPLOYABILITY AND VISUAL SELF-PRESENTATION: A STUDY OF SKILLS, EXPERIENCE, AND DIGITAL PORTFOLIOS - Rahate, Vaishali; Jadhav, Swati Sachin; David, Roopa; Deshpande, Abhijeet; Kumbhare, Bhairavi; Asif, Mohd (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The digitalized recruitment space is becoming more focused on visual self-presentation to transform the perception and assessment of employability. This paper analyzes the connection that exists between skills and experience in the workplace and digital portfolios with respect to the effect of visual storytelling on the hiring opinion. The discussed issue is the disconnect between real and visual capabilities and visually mediated visuals that take the upper hand in online recruitment services. The aim is to investigate the ways through which graduates and early-career professionals create digital portfolios and how employers perceive visual elements together with the reported skills and experience. The analysis approach integrates the contents of the portfolios, and extraction of features through machine learning and recruiter assessment study. The layout structure, imagery, typography, and storytelling of the project are visual elements that are reviewed against confirmed skill sets, internship histories, and showing a performance indicator. Quantitative models are used to evaluate correlations between the quality of visual presentation and shortlisting outcomes, and qualitative interviews are used to evaluate the employer perception of credibility, professionalism, and cultural fit. The results indicate that the perceived value of skills and experience in relation to coherent visual storytelling is stronger and provides a high shortlisting probability even in comparison with technical qualifications of equal weight. Nonetheless, having too much aesthetic focus, which is not supported by evidence, has a detrimental impact on the measurement of trust and employability. The analysis shows the differences in access to visual literacy and design tools, creating a problem regarding the equity of digitally mediated recruitment.